Adaptive Immunity to Francisella tularensis and Considerations for Vaccine Development - Roberts, Lydia M.; Powell, Daniel A.; Frelinger, Jeffrey A. (Frontiers in Cellular and Infection Microbiology, 2018)
Francisella tularensis is an intracellular bacterium that causes the disease tularemia. There are several subspecies of F. tularensis whose ability to cause disease varies in humans. The most virulent subspecies, tularensis, is a Tier One Select Agent and a potential bioweapon. Although considerable effort has made to generate efficacious tularemia vaccines, to date none have been licensed for use in the United States. Despite the lack of a tularemia vaccine, we have learned a great deal about the adaptive immune response the underlies protective immunity. Herein, we detail the animal models commonly used to study tularemia and their recapitulation of human disease, the field's current understanding of vaccine-mediated protection, and discuss the challenges associated with new vaccine development.